Learning of the english language as a competitive advantage for the Professional of Touristic and Hotel Management. Case learning experience in the city of Tonawanda, in State New York, USA - Buitrago Bueno, Gabriela (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (83 páginas) : ilustraciones color, tablas.